Denúncia nos contratos privados de assistência à saúde - Zanetti, Andrea Cristina (2018)
The purposes of this work is understanding the role of termination without cause in long-term contracts and contracts for an indefinite term, as well as their current limits, which are established in particular by the principle of good faith. To such end, in order to direct and deepen the topic, our approach focuses specifically on private healthcare contracts, a contract subject to term that exemplifies the complexity of current contractual relations and demonstrates the process of fragmentation of private law in different microsystems, which also impacts on unilateral notice as a form of termination of the contractual relationship and a kind of unilateral termination for convenience. Generally, in the perspective of unilateral termination without cause, the operability of good faith allows its control to occur in two distinct moments: upon controlling the contractual content (providing guidelines for or restricting unilateral termination) and upon controlling actual exercise of the right (by means of the observance of certain obligations, respect to codes of conduct and repression of the undue, disproportionate and illegitimate use of this form of extinction of the contract). These controls and their consequences are what may result in the invalidity of the contractual provision, the right to indemnification and even in maintaining or extending the effectiveness of the contract. This demonstrates the current dimension attributed to good faith in the control of unilateral termination, which is gradually intensified depending on the contractual microsystem involved and whether it is a business or existential (essential) contract. In view of this new perspective, the issue of unilateral termination in contracts governed by the microlegal framework of Law 9,656/1998 (Health Plans Act) is presented from the perspective of the speciality and essentiality of its contractual object, which influence the operability of good faith and requires acknowledgment of the microsystem in which it is inserted, and which also needs to relate to the other subsystems that form Private Law, in a coherent and systematic interpretation in the search for possible solutions to the issue, mainly due to the fact that the aforementioned law does not clearly deal with this form of termination regarding the different parties involved in private healthcare contracts